A Pilot Study Exploring the Use of an Online Pre-Composed Receptive Music Experience for Students Coping with Stress and Anxiety. (18th October 2018) - Fiore, Jennifer
Abstract: College/university students face many stressors as they balance their studies, work, personal relationships, and personal/family expectations. Music therapy students have additional stressors related to academic, musical, and clinical development. College/university students have increased mental health needs compared to previous generations, with volume impacting institutions. The objective of this study was to investigate the use of an online receptive music experience for music therapy students' stress and anxiety levels, and also to examine if a particular musical element was perceived as more beneficial in decreasing stress and anxiety. Twenty-three participants (undergraduate and graduate-equivalency music therapy students) engaged in a study offered online. Measures included the Spielberger State Trait Anxiety Inventory (STAI), the Stress Overload Scale (SOS), and a post-experience survey about musical element effectiveness. Results indicated that the receptive music experience elicited a significant decrease in students' stress and anxiety levels. A subscale analysis of the SOS indicated that participants had a significant decrease in personal vulnerability, and an overall decrease in event load, though this decrease was not significant. Participants' reflections about the musical elements indicated that melody was most effective and instrumentation was least effective, with groups of elements also indicated. Pilot study results support further research investigating the use of an online receptive music experience for students, professionals, and music therapy clients as a way to manage acute stress.